Cytometry‐based single‐cell analysis of intact epithelial signaling reveals MAPK activation divergent from TNF‐α‐induced apoptosis in vivo - Alan J Simmons; Amrita Banerjee; Eliot T McKinley; Cherie' R Scurrah; Charles A Herring; Leslie S Gewin; Ryota Masuzaki; Seth J Karp; Jeffrey L Franklin; Michael J Gerdes; Jonathan M Irish; Robert J Coffey; et al. (Molecular Systems Biology)
Abstract Understanding heterogeneous cellular behaviors in a complex tissue requires the evaluation of signaling networks at single‐cell resolution. However, probing signaling in epithelial tissues using cytometry‐based single‐cell analysis has been confounded by the necessity of single‐cell dissociation, where disrupting cell‐to‐cell connections inherently perturbs native cell signaling states. Here, we demonstrate a novel strategy (Disaggregation for Intracellular Signaling in Single Epithelial Cells from Tissue—DISSECT) that preserves native signaling for Cytometry Time‐of‐Flight (CyTOF) and fluorescent flow cytometry applications. A 21‐plex CyTOF analysis encompassing core signaling and cell‐identity markers was performed on the small intestinal epithelium after systemic tumor necrosis factor‐alpha (TNF‐α) stimulation. Unsupervised and supervised analyses robustly selected signaling features that identify a unique subset of epithelial cells that are sensitized to TNF‐α‐induced apoptosis in the seemingly homogeneous enterocyte population. Specifically, p‐ERK and apoptosis are divergently regulated in neighboring enterocytes within the epithelium, suggesting a mechanism of contact‐dependent survival. Our novel single‐cell approach can broadly be applied, using both CyTOF and multi‐parameter flow cytometry, for investigating normal and diseased cell states in a wide range of epithelial tissues.